Mycobacterium tuberculosis PE/PPE proteins enhance the production of reactive oxygen species and formation of neutrophil extracellular traps - García-Bengoa, María; Meurer, Marita; Stehr, Matthias; Elamin, Ayssar A.; Singh, Mahavir; Oehlmann, Wulf; Mörgelin, Matthias; von Köckritz-Blickwede, Maren (Frontiers in Immunology, 2023)
Neutrophil granulocytes predominate in the lungs of patients infected with Mycobacterium tuberculosis (Mtb) in earlier stages of the disease. During infection, neutrophils release neutrophil extracellular traps (NETs), an antimicrobial mechanism by which a DNA-backbone spiked with antimicrobial components traps the mycobacteria. However, the detailed mycobacterial factors inducing NETs are still not entirely clear. Proteins from the proline-glutamic acid (PE)/proline-prolineglutamic acid (PPE) family are fundamental to Mtb pathophysiology and virulence. Here, we report for the first time that Mtb proteins PE18, PE31 and PPE26 induced NET formation in human neutrophils, a specific novel function of these PE/PPE antigens. Thus, we investigated NET induction in human primary blood-derived neutrophils after 3h stimulation with PE18, PPE26 and PE31, and formation of NETs was assessed using confocal fluorescence microscopy. Intracellular ROS levels and cell necrosis were estimated by flow cytometry resulting in increased levels of ROS induced by all three candidates, which was also correlating with an enhanced formation of NETs. This effect was furthermore boosted in presence of phorbol-12-myristat-13-acetat (PMA), a well-known enhancer of NADPH oxidases. However, neutrophils remained intact after incubation with the PE/PPE candidates, an indicator of vital NET formation that was later confirmed by transmission electron microscopy. These results provide insights relevant to a better understanding of host-pathogen interaction during Mtb infection.